(3JhKjb YQi GdEjeGf aj JaVjd MHjH GdQMefs - (3GHf GdHGQRj , gHI Gddg Hf YHO GdQMje Hf EHQGgje, TQa GdOjf CHhGdbGSe,J (B738 (3g` s ((3Ydi Hf GdHjZGfi s)
(3ChdgG (B:s
(3jHOC HGdcdGe Ydi GdQcf GdKGdK ai EZGKJg ef ESJZGK Hg ai MjGJg hHYO ehJg s
(3BNQgG (B:s
(3ced eGLeYJg hGfJNHJg hGNJQJg hQJHJg ef aVGFd gPG GdfHi Gddge Ud Ydi gPG GdfHi GdcQje jGQMef jG QMje s
(3GdLRA GdKGfi ef fSNI KGfjIs
(3HBNQgG ebGHdI Ydi iGdCUd GdefJSN efgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B73 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B139s
Keywords: (3GdJGQjNs